The Relationship Between Student Learning Motivation and Student Perceptions on Teacher Learning and Science Learning Outcomes at MTS Negeri 2 Surakarta - Kusuma, Annisa Nandia; Kusumadani, Annur Indra (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The purpose of this research is to determine the relationship between student learning motivation and student perceptions of teacher learning with student learning outcomes. The research method used is a survey method with correlational analysis. The population used was students in class VIII of the Special Science Class Program at MTs Negeri 2 Surakarta. The sampling technique is a sample population with a sample of 83 students, data collection techniques are carried out using questionnaires, interviews and documentation. The results of this study show that there is no significant relationship between student learning motivation and learning outcomes and a correlation of 0.000 (0%). There is also no significant relationship between student perceptions of teacher learning and student learning outcomes and the correlation is -0.124 (1.5%). And there is no significant relationship between learning motivation and student perceptions of teacher learning on learning outcomes and the correlation is 0.136. The contribution of learning motivation and student perceptions of teacher learning to student learning outcomes was 1.84% and 98.16% influenced by other factors not researched. The results of this research indicate that student learning motivation and student perceptions of teacher learning do not improve student learning outcomes.